Fundraising in University Libraries in Delta State - Ogbomo, Monday O.; Adomi-Erorote, Dorothy A. (Communicate: Journal of Library and Information Science, 2025)
This study instigated fundraising in university libraries in Delta state. Three research questions were raised to ascertain the level of librarian’s understanding of fundraising in university libraries; investigate fundraising activities carried out in university libraries; and identify challenges university libraries face in fundraising initiatives. The result revealed that: librarians in university libraries in Delta state have a high level of understanding of fundraising (56%); they are not fully engaged in fundraising activities as the aggregate mean is lower than the criterion mean of 2.50, which signifies that the extent of fundraising activities in university libraries is low; librarians in university libraries are faced with challenges such as limited budget and difficulty engaging donor. Consequently, the study recommends that adequate budget should be made for libraries to fully engage in fundraising, there is need for university parent body to carefully craft a realistic budget that takes into account a variety of expenses, including staffing, fundraising event-planning costs and to support fundraising activities in university libraries. Libraries should seek corporate sponsors; host fundraising events; and renting out meeting space to other organizations. The study employed the descriptive survey design. The population comprised of 113 librarians in the university libraries in Delta State. The stratified sampling technique was adopted. The instrument for data collection is structured questionnaire titled “Fundraising in University Libraries in Delta State (FULQ). The data collected was analysed using descriptive statistics such as frequency count and mean.